2019
DOI: 10.1021/acsami.9b14111
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Thermal Desorption in a 3D Printed Multifunctional Composite CO2 Sorbent with Embedded Heating Capability

Abstract: Efficient removal of CO2 from enclosed environments is a significant challenge, particularly in human space flight where strict restrictions on mass and volume are present. To address this issue, this study describes the use of a multimaterial, layer-by-layer, additive manufacturing technique to directly print a structured multifunctional composite for CO2 sorption with embedded, intrinsic, heating capability to facilitate thermal desorption, removing the need for an external heat source from the system. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Manufacturing method for multifunctional adsorbent conductor filament and corresponding thermal properties under different applied voltages. Reproduced with permission from ref . Copyright 2019 American Chemical Society.…”
Section: Printing Strategies Of Structured Adsorbents and Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturing method for multifunctional adsorbent conductor filament and corresponding thermal properties under different applied voltages. Reproduced with permission from ref . Copyright 2019 American Chemical Society.…”
Section: Printing Strategies Of Structured Adsorbents and Catalystsmentioning
confidence: 99%
“…Moreover, the authors also demonstrated that, by 3D printing materials with different functionalities, a composite which retains both materials' properties can be produced. In a similar study, Thompson et al 125 3D-printed two functional inks, where ink one contained zeolite 13X adsorbents and ink two contained conductive silver nanoparticles, to form adsorptive filaments that could be regenerated via electric swing. This process, which is shown in Figure 19, can be considered of high importance as it demonstrated 3D printing's ability to generate a multifunctional material by depositing two inks into a single scaffold.…”
Section: Formulation By Direct Ink Writing Of Presynthesized Adsorben...mentioning
confidence: 99%
“…Both the diameter of the parallel channels and the density per crosssectional area of monoliths are controllable. Most recently, three-dimensional (3D) printing or additive manufacturing technique has gained worldwide attention and has been applied for fabrication of 3D-printed monoliths including zeolites (e.g., 5A and 13X) and MOFs (MOF-74-Ni and UTSA-16-Co (Thakkar et al, 2016;Thakkar et al, 2017a;Thakkar et al, 2017b;Thakkar et al, 2018;Nguyen et al, 2019;Regufe et al, 2019;Thompson et al, 2019). Compared FIGURE 7 | CO 2 capacity reported in the literature with different support at different PEI loading and temperature for CO 2 capture from (A) pure CO 2 and (B) from simulated air with about 400 ppm CO 2 along with the insets showing the amine efficiency (A.E., mol-CO 2 /mol-N).…”
Section: Adsorptionmentioning
confidence: 99%
“…One successful application of this concept was already reported in Table 2. In this study, Thompson et al (2019) used DIW with dual extruders to produce a sorbent structure with integrated heating. The key to the success of this example is the similarity of the two inks, as the conductive ink (used for resistive heating) was produced by adding silver microflakes to the sorbent formulation.…”
Section: Multi-materials Printingmentioning
confidence: 99%